2015
DOI: 10.1111/oik.02233
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and phenological responses of dwarf shrubs to the depth and properties of snow

Abstract: Snow is known to have a major impact on vegetation in arctic ecosystems, but little is known about how snow affects plants in boreal forests, where the snowpack is uneven due to canopy impact. The responses of two dwarf shrubs, the evergreen Vaccinium vitis‐idaea and the deciduous V. myrtillus, to snow conditions were studied in a snow manipulation experiment in southern Finland. The thermal insulation of the snowpack was expected to decrease with partial removal or compression of the snow, while addition of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 57 publications
5
25
0
1
Order By: Relevance
“…The two most common dwarf shrubs of the understorey, V. myrtillus and V. vitis-idaea, showed abundant discoloration of leaf and stem tissue and partly reduced growth, especially in the short-term treatment. Both discoloration and growth reduction are common signs of frost damage in woody plants (Sakai & Larcher 1987;Gu et al 2008) and have previously been observed in these species if exposed to an earlier snowmelt or insufficient snow depth (Raatikainen & V€ anninen 1988;Wipf 2009;Gerdol et al 2013;Wheeler et al 2014;Saarinen et al 2015). We generally found V. myrtillus to be more sensitive than V. vitis-idaea.…”
Section: P L a N T R E S P O N S E S T O A Nsupporting
confidence: 78%
See 2 more Smart Citations
“…The two most common dwarf shrubs of the understorey, V. myrtillus and V. vitis-idaea, showed abundant discoloration of leaf and stem tissue and partly reduced growth, especially in the short-term treatment. Both discoloration and growth reduction are common signs of frost damage in woody plants (Sakai & Larcher 1987;Gu et al 2008) and have previously been observed in these species if exposed to an earlier snowmelt or insufficient snow depth (Raatikainen & V€ anninen 1988;Wipf 2009;Gerdol et al 2013;Wheeler et al 2014;Saarinen et al 2015). We generally found V. myrtillus to be more sensitive than V. vitis-idaea.…”
Section: P L a N T R E S P O N S E S T O A Nsupporting
confidence: 78%
“…As such, snow is a critical regulator of understorey vegetation health and composition (Rasmus, Lundell & Saarinen ; Kreyling, Haei & Laudon ; Saarinen et al . ) as well as soil processes, and a lack of snow has been shown to alter carbon and nutrient fluxes into the next growing season (Groffman et al . ,b, , ; Olsson & Falkengren‐Grerup ; Öquist & Laudon ; Haei et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many observational and experimental studies have highlighted the regulative role of snow in multiple biological functions and ecological properties: e.g. vegetative biomass and growth (Choler 2015), vascular plant species richness and assemblages (Odland andMunkejord 2008, Carlson et al 2015), soil microbial activity and composition (Schimel et al 2004, Zinger et al 2009), overwintering survival (Rapacz et al 2014), root dynamics and mortality (Templer 2012), and photosynthetic capacity (Saarinen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…When low freezing temperatures occur or the leaves are covered by deep snow, the actual rates of CO 2 assimilation are probably low (Saarinen et al, 2015). However, our previous results show that the evergreen dwarf shrub Vaccinium vitis-idaea can attain a net gain in carbon during the winter months (Lundell et al, 2008), and the species is able to up-regulate its photosynthesis rapidly during a mild spell (Saarinen et al, 2011).…”
Section: Discussionmentioning
confidence: 96%